2018
DOI: 10.3390/nu10091315
|View full text |Cite
|
Sign up to set email alerts
|

Tocotrienol-Rich Vitamin E from Palm Oil (Tocovid) and Its Effects in Diabetes and Diabetic Nephropathy: A Pilot Phase II Clinical Trial

Abstract: Tocotrienol-rich vitamin E from palm oil (Tocovid) has been shown to ameliorate diabetes through its superior antioxidant, antihyperglycemic, and anti-inflammatory properties in diabetic rats. This study aimed to investigate the effects of Tocovid on diabetic nephropathy in patients with type 2 diabetes. Baseline parameters of potential subjects such as HbA1c, blood pressure, Advanced Glycation Endproduct (AGE), soluble receptor for AGE (sRAGE), Nε-Carboxymethyllysine (Nε-CML), and Cystatin C were assessed for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 36 publications
0
39
0
Order By: Relevance
“…Interestingly, a recent clinical trial reported the beneficial effects of supplementation with the poorly-studied tocotrienol-rich vitamin E from palm oil (Tocovid) in DKD patients. Tocotrienols have been shown to have significantly more potent antioxidant properties compared to tocopherol with superior antiglycaemic, anticholesterolaemic, anti-inflammatory, neuroprotective, and cardioprotective properties 53 .…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, a recent clinical trial reported the beneficial effects of supplementation with the poorly-studied tocotrienol-rich vitamin E from palm oil (Tocovid) in DKD patients. Tocotrienols have been shown to have significantly more potent antioxidant properties compared to tocopherol with superior antiglycaemic, anticholesterolaemic, anti-inflammatory, neuroprotective, and cardioprotective properties 53 .…”
Section: Discussionmentioning
confidence: 99%
“…Our team previously reported in our interim analysis, that 2 months of high-dose supplementation resulted in a reduction in serum creatinine compared with placebo. 16…”
Section: Methodsmentioning
confidence: 99%
“…15 Tan et al . found that 2 months of supplementation of tocotrienol-rich vitamin E as Tocovid significantly reduced serum creatinine in patients with DN, but not HbA1c, urine albumin:creatinine ratio (UACR), AGE, RAGE, Nε-CML, or Cystatin C. 16…”
Section: Introductionmentioning
confidence: 97%
“…The beneficial effects of antioxidant supplementation on diabetic nephropathy with micro or macroalbuminuria were demonstrated in the past [25], and recent studies confirmed the potential application of tocotrienols and tocopherols in patients with diabetic nephropathy [26]. In addition, vitamin E supplementation in patients with ESRD and pre-existent cardiovascular disease seems to reduce even the risk of fatal and non-fatal myocardial infarction [27], confirming the concomitant renal and systemic beneficial effects of vitamin E supplementation acting on multiple pathways, such as inflammation, vascular health, and oxidative stress.…”
Section: Diabetic Nephropathy and Vitamin Ementioning
confidence: 99%